International Electron Devices Meeting 1998. Technical Digest (Cat. No.98CH36217)
DOI: 10.1109/iedm.1998.746461
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of raised and Schottky source/drain MOSFETs using a novel tunneling contact model

Abstract: We present, for the first time, a physical contact tunneling model that is critical for studying the increasingly important contact behavior in future scaled CMOS. The tunneling processes are self-consistently treated with all current transport in the semiconductor. With this new model, we compared the performance of raised S/D and Schottky S/D MOSFETs. Both raised S/D and Schottky S/D MOSFETs can be designed to give good short-channel characteristics. Our analyses show that despite the lower sheet resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 4 publications
0
30
0
Order By: Relevance
“…It is also important to note that a computational issue associated with using low doped layers in the ITO(n + )/a-Si:H(p) junction is that the non-local band to band tunneling model being used suffers from convergence issues when the layers are completely depleted. Previous simulation studies conducted by Kanevce et al [44,18] and Kirner et al [52] showed the importance of the tunneling mechanism at the ITO(n + )/a-Si:H(p) junction. Thus, we arrive at the conclusion that; 1) a high workfunction achieved by low doping in the ITO(n + ) layer will lead to reduced tunneling at the ITO(n + )/a-Si:H(p) interface which will result in an increased ρc, and 2) a low workfunction achieved by high doping in the ITO(n + ) layer will lead to increased tunneling current and thus a lower ρc .…”
Section: Variation Of Ito Dopingmentioning
confidence: 98%
“…It is also important to note that a computational issue associated with using low doped layers in the ITO(n + )/a-Si:H(p) junction is that the non-local band to band tunneling model being used suffers from convergence issues when the layers are completely depleted. Previous simulation studies conducted by Kanevce et al [44,18] and Kirner et al [52] showed the importance of the tunneling mechanism at the ITO(n + )/a-Si:H(p) junction. Thus, we arrive at the conclusion that; 1) a high workfunction achieved by low doping in the ITO(n + ) layer will lead to reduced tunneling at the ITO(n + )/a-Si:H(p) interface which will result in an increased ρc, and 2) a low workfunction achieved by high doping in the ITO(n + ) layer will lead to increased tunneling current and thus a lower ρc .…”
Section: Variation Of Ito Dopingmentioning
confidence: 98%
“…The energy of carriers, the occupied and free states in both sides of the barrier, and the energy barrier are therefore crucial parameters. As described by Ieong et al [45], the tunneling for transport of electrons and holes is, therefore, related to the local generation rate G as follows:…”
Section: B Tunnelingmentioning
confidence: 99%
“…where is the reduced Planck constant and ψ e (r) is the electrostatic potential in terms of potential barrier profile along the position r for electrons, and m e are the tunneling masses of electrons and holes. Technology computer-aided design (TCAD) Sentaurus considers a complex state-of-the-art model detailed in [45] and [52] to describe transport through heterointerfaces by tunneling. However, the purpose of this paper is to only identify parameters affecting the collection of carriers through tunneling oxide in poly-Si based CSCs.…”
Section: B Tunnelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy range in this example is taken to extend above the barrier from the conduction band edge at the CN-contact interface E c (0) to a maximum energy chosen to capture all significant carriers (E max = µ S + 20kT ). The tunneling current can be conveniently incorporated into our multi-scale model by representing it as a generation rate, as described in [13] and adapted as follows (the electron case is given as an example here, however only minor modifications are necessary to treat holes): transforming the continuity equation,…”
Section: Modelmentioning
confidence: 99%